Description of the metoposaurid Anaschisma browni from the New Oxford Formation of Pennsylvania. (September 2021) - Gee, Bryan M.; Jasinski, Steven E.
Abstract: Metoposaurids are a widespread and ubiquitous constituent of Late Triassic non-marine paleoenvironments. In North America, this group is practically the only large-bodied temnospondyl clade, and is particularly well documented from the American southwest and south-central regions (Arizona, New Mexico, Texas). However, metoposaurids are poorly documented from eastern North America, with fragmentary, doubtfully diagnostic historical material such as " Dictyocephalus elegans " Leidy, 1856 and " Eupelor durus " Cope, 1866 . The Zions View (early Norian?) locality in Pennsylvania preserves more-complete material, which previous workers noted as belonging to " Buettneria perfecta " Case, 1922 (= Anaschisma browni Branson, 1905 ). However, the material has never been described in a fashion that characterizes the anatomy or that justifies the taxonomic assignment, yet it would represent the most complete material in eastern North America and a substantial expansion of this taxon's geographic range. Here we redescribe the Zions View metoposaurid material in detail, differentiating it from Calamops paludosus Sinclair, 1917, the only other Late Triassic temnospondyl from the eastern seaboard, and demonstrating confident affinities with A . browni . Our study is the first to properly justify the taxonomic referral, underscoring the broader importance of proper documentation of voucher specimens, especially for potential geographic outliers. Anaschisma browni is thus the most widely dispersed metoposaurid. Its easternmost documentation underscores the importance of the undersampled and understudied metoposaurid record on the eastern seaboard for understanding the development of a metoposaurid zone of exclusivity in North America and demonstrates the need for further exploration to refine conceptualizations of Late Triassic tetrapod evolution.